Does the Coronavirus Anxiety Scale Measure Coronaphobia the Same Way for Mourners With and Without Dysfunctional Grief? - Lobos-Rivera, Marlon Elías (2023)
Deaths from COVID-19 have exceeded 6.5 million people globally. Although many people are mourning the loss of loved ones to this deadly disease, little is known about the validity of measuring coronavirus-related anxiety with this particular group of people. Therefore, the objective of this study is to determine if the coronavirus anxiety scale (CAS) measures the coronaphobia construct the same way for mourners with and without dysfunctional levels of grief. The results indicated that the four-item version of the CAS has acceptable fit indices and is partially invariant between people with dysfunctional and non-dysfunctional grief. Moreover, the CAS demonstrated adequate criterion validity and reliability with this group of bereaved adults. In conclusion, the CAS can be used to measure anxiety due to COVID-19 in people who are going through dysfunctional and non-dysfunctional grieving processes.